The Impact of Regular Sport Participation on Bone Health and Osteoporosis Prevention: A Narrative Review - Kudła, Martyna; Kociuba, Julia; Kruczek, Zuzanna; Kurcińska , Julia; Kurciński, Szymon; Łobaza, Paulina; Zając , Gabriela; Krawczyk , Agata; Czechowicz, Paweł; Czechowicz, Justyna; et al. (Quality in Sport, 2026)
Background: Osteoporosis is a global public health challenge linked to population aging and sedentary lifestyles. Non-pharmacological prevention is essential. Aim: The aim of this study was to review current scientific literature on the impact of regular sport participation on bone health, with emphasis on its role in the prevention and treatment of osteoporosis. Material and Methods: A review of publications (2021–2026) from PubMed was conducted, including meta-analyses and clinical trials on the relationship between mechanical loading and bone mineral density (BMD). Results: High-impact and multi-directional sports (volleyball, basketball) provide the most potent osteogenic stimuli. In postmenopausal women, high-intensity resistance training (80-85% 1RM) mitigates bone loss and improves Health-Related Quality of Life (HRQoL). Sport also reduces fall risk in the elderly by enhancing postural stability. Conclusions: Regular sport participation is the "gold standard" for osteoporosis prevention. Optimizing peak bone mass in youth and maintaining skeletal integrity in old age are vital. Interdisciplinary collaboration is necessary to implement these findings into public health practice.